Good Governance for Efficient Public Services Responsive and Transparent - Ni Putu Tirka Widanti (ijd-demos, 2022)
AbstractThe provision of goods, services, and administrative services by public service providers is one example of how the implementation of public services by the state is an attempt to meet the fundamental requirements and uphold the civil rights of all citizens. A conceptual framework for improving the ideology, paradigm, culture, and management of a government in order to achieve high performance is called "good governance." The existence of cultural constraints within the bureaucracy is the factor that has the greatest impact on the quality of public services. In addition, there is a component in the behavior of the apparatus that does not reflect the behavior of serving but, on the other hand, tends to show the behavior of wanting to be served. This component is known as the "wanting to be served factor." The purpose of this research is to investigate how effective governance can contribute to the delivery of public services that are also responsive, open, and efficient. In this investigation, a qualitative strategy is combined with a descriptive research approach. The findings of the study indicate that the implementation of good governance in the improvement of public services can be carried out in accordance with the principles of efficiency, responsiveness, and transparency.Keywords: Public Service, Good Governance, Efficient, Responsive, Transparent. AbstrakPenyediaan barang, jasa, dan pelayanan administrasi oleh penyelenggara pelayanan publik merupakan salah satu contoh bagaimana penyelenggaraan pelayanan publik oleh negara merupakan upaya untuk memenuhi kebutuhan dasar dan menjunjung tinggi hak-hak sipil seluruh warga negara. Kerangka konseptual untuk meningkatkan ideologi, paradigma, budaya, dan manajemen suatu pemerintahan untuk mencapai kinerja yang tinggi disebut “pemerintahan yang baik”. Adanya kendala budaya dalam birokrasi merupakan faktor yang paling besar pengaruhnya terhadap kualitas pelayanan publik. Selain itu, terdapat komponen perilaku aparatur yang tidak mencerminkan perilaku melayani tetapi sebaliknya cenderung menunjukkan perilaku ingin dilayani. Komponen ini dikenal sebagai "faktor ingin dilayani". Tujuan dari penelitian ini adalah untuk menyelidiki bagaimana pemerintahan yang efektif dapat berkontribusi pada pemberian layanan publik yang juga responsif, terbuka, dan efisien. Dalam penelitian ini, strategi kualitatif dipadukan dengan pendekatan penelitian deskriptif. Temuan penelitian menunjukkan bahwa penerapan good governance dalam peningkatan pelayanan publik dapat dilaksanakan sesuai dengan prinsip efisiensi, daya tanggap, dan transparansi.Kata Kunci: Pelayanan Publik, Good Governance, Efisien, Responsif, Transparan.